"Not for the Weak": The Lived Experience of Women in Romantic Relationships With Incarcerated Individuals. (November 2022) - Tadros, Eman; Presley, Sarah; Gomez, Eunice
The impacts of incarceration extend to the entire family system. The relational impact of incarceration is compounded by the increasing stressors romantic partners experience during incarceration. Romantic relationships are multifaceted and necessitate honoring the voices at the center of experience that are often silenced. Individuals in a romantic relationship with an incarcerated individual were interviewed to understand their lived experience using a phenomenological approach. Five themes (stigma, mental health services, suggestions, impact of incarceration, and limitations) emerged from the eight interviews. Implications are discussed to advocate for this population through research and clinical work.